A decentralized learning-based approach to classify colorectal cancer using Deep Learning Leveraging XAI - Mubin, Kazi Ehsanul; Arthi, Noshin Tabassum; Rahman, Junayed; Rafi, G. M.; Sheja, Tahsina Tanzim (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.